Current Update of Clinical Therapeutic Strategies for Colon-Targeted Delivery Systems - Widiani Batubara, Risa; Chany Saputri, Fadlina; Iswandana, Raditya (Pharmaceutical Sciences and Research, 2024)
Oral colon-targeted drug delivery systems represent a significant advancement offering both systemic and local therapeutic effects for a range of intestinal diseases, including irritable bowel syndrome, inflammatory bowel disease, colonic bacterial infections, and colorectal cancer. These systems facilitate the delivery of both small molecules and macromolecular compounds such as peptides, proteins, antibodies, oligonucleotides, RNA, and probiotics. This review provides an up-to-date exploration of the critical factors crucial for the effective design and development of drug delivery systems targeting the colon. The chosen strategy takes into account various aspects of colon physiology that influences the profile of drug release, absorption, dissolution, and stability in the colon, including pH, retention time, presence of enzymes, pressure, presence of reactive oxygen species due to inflammation, and specific receptors. Site-targeted drug release allows for high concentrations in the colon while minimizing systemic adverse effects by reducing or preventing drug absorption in the small intestine.